Method of obtaining gelatin from aquatic animals - Md Yusoff, Fatimah; Bakar, Jamilah; Basri, Mahiran; Ismail, Maznah; Khong, Nicholas Mun Hoe (2013)
The present invention relates to a simple, cost and time effective process of producing gelatin from aquatic animal tissue, which comprises the steps of: (a) treating the cleaned and dehydrated aquatic animal tissue with salt solution, preferably of less than 1.0M; (b) treating biomass obtained after Step (a) with aqueous alkali; (c) washing the alkali-treated biomass with water until the washing water is substantially neutral; (d) treating the neutralized biomass from step (c) with aqueous acid with continuous stirring for up to 4 h; (e) washing the acid-treated biomass with water until the washing water is substantially neutral; (f) extracting with water at pH less or equal to 2 at temperatures in the range of 45°C to 65°C for 6 to 8 h; (g) dialysing the gelatin obtained from step (f) against neutral buffer or deionised distilled water for at least 24 hours; (h) removal of water from the gelatin obtained until moisture content of the resulting gelatine is less than 13%. The process provides a gelatine having excellent properties, such as quality, appearance, gel strength etc., suitable for use in pharmaceutical, cosmeceutical, food and photography products.